Quantitative determination of the Cu species, acid sites and NH3-SCR mechanism on Cu-SSZ-13 and H-SSZ-13 at low temperatures. Issue 4 (23rd January 2020) - Liu, Kuo; Yan, Zidi; Shan, Wenpo; Shan, Yulong; Shi, Xiaoyan; He, Hong
Abstract : The NH3 -SCR mechanism and the number of acid sites and various Cu species on Cu-SSZ-13 and H-SSZ-13 were quantitatively determined. Abstract : The adsorption amounts of NO, NO2, and NH3, the number of adsorption sites including different Cu species and acid sites and the reaction mechanism of NH3 -SCR on Cu-SSZ-13 synthesized by a one-pot synthesis method and H-SSZ-13 at low temperatures were determined in the present study by a quantitative analysis method, the transient response method (TRM). NH3 covered most of the surface sites on both Cu-SSZ-13 and H-SSZ-13 during the NH3 -SCR reaction. NO2 adsorbed on the SSZ-13 zeolite support, and NO adsorbed on Cu sites. The presence of O2 promoted NO adsorption on Cu sites. However, H-SSZ-13 could not activate NO either in the presence or absence of O2 . Cu-SSZ-13 was composed of 12 μmol g −1 (Z − Cu 2+ )2 –O2, 148 μmol g −1 Z − Cu 2+ O2 ˙ and 252 μmol g −1 Z − Cu 2+ OH for NO and NH3 adsorption, 176 μmol g −1 Z2 Cu 2+ and 864 μmol g −1 Z–OH for NH3 adsorption, and 1360 μmol g −1 Z and Z–O 2− for NO2 adsorption, while H-SSZ-13 consisted of 1193 μmol g −1 Z–OH for NH3 adsorption and 807 μmol g −1 Z and Z–O 2− for NO2 adsorption. On H-SSZ-13, two NH3 molecules adsorbed on one acid site, and the only reaction pathway was NO reacting with NH4 NO3 to form N2, H2 O and NO2 ("NH4 NO3 pathway") during standard and fast SCR. On Cu-SSZ-13, besides the "NH4 NO3 pathway" on the SSZ-13 support, reactions between nitrite formed by the NO adsorbed on Z − Cu 2+ –O2 ˙, (Z − Cu 2+ )2 –O2 and Z − Cu 2+ OH and adsorbed NH3 to form N2 and H2 O ("nitrite pathway") also occurred. Cu-SSZ-13 exhibited higher NH3 -SCR activity than H-SSZ-13 because of the reaction between adsorbed NH3 and nitrite formed by NO adsorbed on the Cu sites in the CHA cages.